Manganese ferric sodium phosphate pyrophosphate positive electrode material as well as preparation method and application thereof

By adopting the preparation method of Na3 (Mn0.8Fe0.2)2 (PO4) (P2O7), the problem of poor electronic conductivity and electrochemical performance of the positive electrode material of sodium ion battery is solved, high specific capacity, working voltage and cycling stability are achieved, and the overall performance of sodium ion battery is improved.

CN119637833AInactive Publication Date: 2025-03-18SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411610289.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The development of high-performance positive electrodes of existing sodium ion batteries has problems of poor electronic conductivity and electrochemical performance, which limits its development.

Method used

Using the preparation method of sodium manganese pyrophosphate positive electrode material Na3 (Mn0.8Fe0.2)2(PO4) (P2O7), the positive electrode material is obtained by dissolving sodium dihydrogen phosphate, manganese acetate and ferric nitrate in water, adding citric acid monohydrate, heating and stirring, and freeze-drying, and then pre-calcined under an inert atmosphere and secondary calcined under a reducing atmosphere.

Benefits of technology

The specific capacity, working voltage, rate performance and cycle stability of the positive electrode material of ferromanganese pyrophosphate phosphate is improved, and the energy density of the matching whole battery can reach 226Wh/kg, which has high practical value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637833A_ABST
    Figure CN119637833A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium manganese ferric phosphate pyrophosphate positive electrode material and a preparation method and application thereof. The chemical formula of the sodium ion positive electrode material is Na3 (Mn0. 8Fe0. 2) 2 (PO4) (P2O7), the sodium ion positive electrode material is of a regular nanosheet structure, the particle size is 2 microns, and the compaction density is 2.3-2.5 g / cm < 3 >. According to the method, the ferromanganese source precursor is synthesized under the assistance of a sol-gel method and freeze drying, various conditions in the reaction process are easy to control, and the repeatability of the product is relatively good. The sodium manganese ferric phosphate pyrophosphate positive electrode material synthesized by the method is nanoparticles which are uniformly distributed; and when being used as the positive electrode material of the sodium ion battery, the material has the advantages of good air stability, high working voltage (3.4 V), good rate capability and stable cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium batteries, and in particular to a sodium manganese iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] As global environmental and energy issues continue to intensify, countries have put forward higher requirements for vigorously developing new energy storage and reducing carbon emissions. Among various new energy storage, lithium-ion battery energy storage in electrochemical energy storage is particularly prominent due to its advantages such as high energy density, high power density and good cycle life. However, due to the uneven distribution of lithium resources and the need for large-scale imports of lithium resources in my country, we urgently need to find other energy storage systems that are not limited in resources and safe and reliable to replace lithium-ion batteries. Sodium-ion batteries have attracted much attention due to their advantages such as unlimited resources, low cost and industrial compatibility with lithium-ion batteries. However, the development of high-performance positive electrodes for sodium-ion batteries is still the core obstacle to the development of sodium-ion batteries.

[0003] In order to solve the above problems, researchers have turned their attention to layered oxides, polyanionic compounds, and Prussian blue compounds. Among them, the phosphate polyanionic compound Na3Mn2(PO4)(P2O7) has attracted much attention due to its high stability and high performance. However, the poor electronic conductivity and electrochemical properties of Na3Mn2(PO4)(P2O7) have strictly restricted its development. By replacing part of Mn with Fe, the electrochemical performance can be effectively improved, and the storage of sodium ions can be effectively improved. However, Mn 2+ Problems such as full battery degradation caused by dissolution remain to be solved.

[0004] Therefore, how to improve the electrochemical performance of polyanion compounds while achieving the development of high performance of full batteries is also a problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and provide a sodium ferromanganese phosphate pyrophosphate positive electrode material.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned positive electrode material.

[0007] Another object of the present invention is to provide applications of the above-mentioned positive electrode material.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing sodium ferromanganese phosphate pyrophosphate positive electrode material comprises the following steps:

[0010] (1) dissolving sodium dihydrogen phosphate, manganese acetate and ferric nitrate in water, adding citric acid monohydrate, heating and stirring, and drying to obtain a mixed precursor;

[0011] (2) Pre-calcining the mixed precursor obtained in step (1) under an inert atmosphere, cooling it, and then calcining it again under a reducing atmosphere to finally obtain the sodium manganese iron phosphate pyrophosphate positive electrode material.

[0012] The molar ratio of sodium dihydrogen phosphate, manganese acetate and ferric nitrate in step (1) is 1-5:1-3:0.1-1; preferably 3:1.6:0.4.

[0013] The ratio of the amount of citric acid monohydrate described in step (1) to the total amount of sodium dihydrogen phosphate, manganese acetate and ferric nitrate is 1-2:1-2; preferably 1:1.

[0014] The heating and stirring conditions in step (1) are stirring at 70-90° C. for 20-40 min; preferably stirring at 80° C. for 30 min.

[0015] The drying in step (1) is freeze drying; preferably, liquid nitrogen freeze drying is used for 12 hours.

[0016] The inert atmosphere in step (2) is an argon atmosphere.

[0017] The pre-calcination conditions of step (2) are to heat the material to 250-350°C at a rate of 3-7°C / min and calcine for 4-6h; preferably, to heat the material to 300°C at a rate of 5°C / min and calcine for 5h.

[0018] The reducing atmosphere in step (2) is a hydrogen-argon mixed atmosphere; preferably a hydrogen-argon mixed atmosphere with a ratio of hydrogen to argon of 5:95, with a flow rate of 1.5 L / min.

[0019] The calcination conditions in step (2) are to heat the material to 600-700° C. at a rate of 3-7° C. / min and calcine for 8-12 h; preferably, to heat the material to 650° C. at a rate of 5° C. / min and calcine for 10 h.

[0020] A sodium manganese iron phosphate positive electrode material, the composition of which is Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7).

[0021] The sodium manganese iron phosphate pyrophosphate positive electrode material is prepared by the above preparation method.

[0022] The application of the sodium manganese iron phosphate pyrophosphate positive electrode material in the preparation of sodium batteries.

[0023] A sodium battery, the positive electrode of which comprises a sodium iron manganese phosphate pyrophosphate positive electrode material.

[0024] The negative electrode material of the sodium battery is hard carbon.

[0025] The positive electrode of the sodium battery is composed of sodium iron manganese phosphate pyrophosphate positive electrode material, Super P and PVDF.

[0026] The sodium battery, the positive electrode also includes a pre-sodium agent; preferably, it also includes a pre-sodium agent sodium oxide or sodium carbonate; more preferably, it also includes 8wt% of the pre-sodium agent sodium oxide or sodium carbonate.

[0027] Compared with the prior art, the present invention has the following advantages and effects:

[0028] (1) The present invention discloses a sodium manganese iron phosphate positive electrode material, whose chemical formula is Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7), the reaction process is easy to control and environmentally friendly, the product has good reproducibility, and the compacted density of the product can reach 2.3g·cm 3 .

[0029] (2) The prepared sodium manganese iron phosphate pyrophosphate positive electrode material has the advantages of high specific capacity, high operating voltage, good rate performance and good cycle stability.

[0030] (3) The energy density of the full battery matched with the pre-sodium treatment technology of the present invention can reach 226Wh / kg, which has high practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the X-ray diffraction pattern of Example 1 of the present invention and Comparative Example 1 with different Fe contents;

[0032] Figure 2 is a refined image of the unit cell structure of sodium manganese iron pyrophosphate in Example 1 of the present invention;

[0033] Figure 3 It is a crystal structure diagram of the sodium manganese iron phosphate pyrophosphate positive electrode in Example 1 of the present invention.

[0034] Figure 4 is a scanning electron microscope image in Example 1 of the present invention;

[0035] Figure 5 It is the rate cycle diagram of different Fe contents of Example 1 and Comparative 1 of the present invention;

[0036] Figure 6 This is a cycle performance curve diagram of Example 2 of the present invention at 1.8-4.3V;

[0037] Figure 7: is a cycle diagram of a sample with an Fe content of 0.4 at different current densities in Example 1 of the present invention;

[0038] Figure 8 It is a charge and discharge curve diagram of a full battery without pre-sodiumization at 1.4-4.3V in Example 3 of the present invention;

[0039] Fig. 9 This is a diagram for determining the optimal amount of sodium oxide (Na2O) added as a pre-sodiumizing agent in Example 3 of the present invention;

[0040] Fig.10 The charge and discharge curve of the full battery pre-sodiumized by adding 8wt% sodium oxide (Na2O) at 1.4-4.3V in Example 3 of the present invention;

[0041] Fig.11 This is a charge and discharge curve diagram of a full battery pre-sodiumized by adding 8 wt% sodium carbonate (Na2CO3) at 1.4-4.3V in Example 3 of the present invention;

[0042] Fig.12 This is a comparison chart of the cycle performance of the soft-pack battery with 8 wt% pre-sodium added in Example 3 of the present invention;

[0043] Fig.13 This is a safety test of the full battery after pre-sodiumization using sodium oxide (Na2O) in comparative example 3 of the present invention. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0045] If no specific experimental conditions are specified in the following embodiments, conventional experimental conditions or experimental conditions recommended by the reagent company are generally followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.

[0046] Example 1

[0047] Anhydrous sodium dihydrogen phosphate (NaH2PO4), manganese acetate (Mn(CH3COO)2) and ferric nitrate (Fe(NO3)3) were weighed and dissolved in deionized water according to the stoichiometric ratio of Na:Mn:Fe=3:2-x:x (x=0, 0.1, 0.2, 0.3, 0.4, 0.5), and then monohydrate citric acid was added as a chelating agent in the same amount as the total amount of transition metal salt substances. After stirring and drying in an 80°C oil bath for 30 minutes, the mixture was freeze-dried for 12 hours with the assistance of liquid nitrogen to obtain a mixed precursor. The mixed precursor was pre-sintered at 300°C for 5h in argon at a heating rate of 5°C / min, and after cooling, it was secondary sintered again at 650°C for 10h in a hydrogen-argon mixed atmosphere (hydrogen: argon=5:95) at a heating rate of 5°C / min, and the gas flow rate used was 1.5L / min, and finally a pure phase of sodium manganese iron phosphate pyrophosphate positive electrode material was obtained.

[0048] The obtained sodium manganese iron phosphate pyrophosphate positive electrode material was characterized, and the experimental results showed that a pure phase sodium manganese iron phosphate pyrophosphate positive electrode material was synthesized using the sol-gel-freeze drying method. Figure 1 The X-ray diffraction spectrum (XRD) shows that no impurity peaks are generated when the Fe content is 0, 0.1, 0.2, 0.3 and 0.4, and when the Fe content increases to 0.5, the material produces a Na4Mn3(PO4)(P2O7) impurity phase. There is no impurity peak in the spectrum of materials with an Fe content below 0.4, and the product purity is high.

[0049] Figure 2 The material Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7) unit cell structure refinement diagram, detailed refinement parameters are shown in Table 1; Figure 3 Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7) crystal structure diagram. The material shows a wider ion channel along the (020) crystal plane, which can effectively increase the diffusion rate of sodium ions in the unit cell. Figure 4 This is a scanning electron microscope image. It can be seen that the sodium manganese iron pyrophosphate has a nanosheet structure. After further compaction, the compaction degree can reach 2.3-2.5 g / cm 3 .

[0050] Table 1Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7) crystal structure refinement results Detailed atomic occupancy information

[0051]

[0052]

[0053] Example 2

[0054] (1) The sodium manganese iron phosphate pyrophosphate positive electrode material (Fe = 0-0.5) obtained in Example 1, Super P, and PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone solvent was dripped into the mixture with a rubber-tipped dropper. After mixing and grinding for 30 minutes, the mixture was evenly coated on an aluminum foil, dried, and cut into electrode pieces with a diameter of 11 mm.

[0055] (2) Using the electrode prepared in step (1) as the positive electrode, sodium foil as the negative electrode, glass fiber as the separator, and 1M NaClO4 dissolved in EC / DEC as the electrolyte, CR-2032 button cells were assembled in air and electrochemical tests were performed.

[0056] In the voltage range of 1.8-4.3V and the current density of 0.1C, the cycle curve of the sodium manganese iron pyrophosphate positive electrode is as follows Figure 5 He Ru Figure 6 As shown. Among them, the material Na3(Mn 0.8 Fe 0.2 The charge / discharge specific capacity of the positive electrode prepared by )2(PO4)(P2O7) at a current density of 0.1C in the first three cycles is 128.82 / 119.96 mAh g -1 、125.98 / 117.6mAh g -1 , 119.98 / 116.4mAh g -1 , indicating that sodium manganese iron phosphate has higher electrochemical performance. The electrochemical performance of materials with low or no Fe addition is poor, and the performance of materials with 0.5 Fe addition is also poor due to the presence of impurities in the final synthesized material. This proves that Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7) has the best performance.

[0057] When the voltage range is 1.8~4.3V and the current density is 0.2C, 0.5C and 1C, Na3(Mn 0.8 Fe 0.2 The cycle performance of the positive electrode prepared by Figure 7As shown. When sodium manganese iron pyrophosphate was cycled for 200 cycles at a current density of 0.2C, the capacity retention rate was 81.2%; when sodium manganese iron pyrophosphate was cycled for 400 cycles at a current density of 0.5C, the capacity retention rate of the sodium manganese iron pyrophosphate positive electrode was 75.2%; when sodium manganese iron pyrophosphate was cycled for 600 cycles at a current density of 1C, the capacity retention rate was 64%. It can be seen that the sodium manganese iron pyrophosphate positive electrode material has excellent electrochemical cycle stability.

[0058] Example 3

[0059] In the previous experiments, sodium foil was used as the negative electrode to assemble a sodium battery to test the electrochemical properties of the positive electrode material. However, in actual production applications, directly using sodium foil to assemble the battery is too expensive and prone to loss of control. Therefore, this embodiment uses a hard carbon negative electrode to test the performance of the positive electrode material under other conditions.

[0060] (1) Commercial hard carbon, Super P and CMC were mixed into a slurry in a mass ratio of 8:1:1, uniformly coated on an aluminum foil, and dried in a forced air drying oven at 80° C. for 8 h to obtain a hard carbon negative electrode sheet;

[0061] (2) Prepare Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7) phosphate pyrophosphate sodium manganese iron positive electrode sheet, the hard carbon negative electrode sheet prepared in step (1) is used as the negative electrode, and 120 μL of electrolyte (1M NaClO4 dissolved in an organic solvent with a volume ratio of EC:DEC=1:1) is added according to the ratio of the negative electrode capacity to the positive electrode capacity of 1.01-1.20. The soft-pack full battery is assembled in a glove under argon protection and electrochemical tests are performed. The test voltage is 1.4-4.3 V and the test current is 0.1 C (1 C = 120 mAh g -1 ).

[0062] The experimental results are as follows Figure 8 and 11 As shown, the full battery has a charge / discharge capacity of 121 / 61 mAh g -1 Since a large amount of active sodium ions are consumed on the negative electrode side of the whole battery, the coulombic efficiency of the whole battery is 55.7%. The energy density of the whole battery calculated based on the positive electrode side is 174Wh / kg, which proves that ordinary hard carbon negative electrodes are difficult to meet the requirements of sodium manganese iron pyrophosphate in practical applications.

[0063] Example 4

[0064] In order to improve the performance of the hard carbon negative electrode in the battery with sodium manganese iron pyrophosphate as the positive electrode material, this embodiment uses sodium oxide (Na2O) and sodium carbonate (Na2CO3) as pre-sodium additives for pre-sodium treatment, and then prepares a full battery and performs electrochemical testing according to the method of Example 3.

[0065] 4.1 Pre-sodium treatment

[0066] (1) Prepare Na3(Mn) by referring to the method of Example 2 0.8 Fe 0.2 )2(PO4)(P2O7) phosphate pyrophosphate sodium manganese iron phosphate positive electrode sheet, and adding 4, 8, 12wt% of sodium oxide (Na2O) as a pre-sodiumizing agent during preparation to obtain a sodium oxide pre-sodiumized phosphate pyrophosphate sodium manganese iron phosphate positive electrode sheet;

[0067] (2) Use the pre-sodiumized sodium manganese iron phosphate pyrophosphate positive electrode obtained in step (1) and 1M NaClO4 electrolyte and sodium foil to assemble a half-cell for testing.

[0068] The results are as follows Fig. 9 As shown in the figure, adding different proportions of sodium oxide (Na2O) as a pre-sodium agent has different effects on the capacity. When the addition amount increases to 12wt%, the capacity of the battery is significantly lower than that of the batteries with 0wt%, 4wt% and 8wt% addition amounts. It can be determined that the optimal addition amount of the pre-sodium agent Na2O in the full battery is 8wt%; by adding 8wt% pre-sodium, the capacity of the full battery can be increased by 19.8mAh / g, and the corresponding energy density can be increased by 23%.

[0069] 4.2 Assembling the full battery

[0070] Referring to the method of Example 3, a full battery was assembled using 8 wt % sodium oxide pre-sodiumized sodium iron manganese phosphate pyrophosphate positive electrode sheets and electrochemical tests were performed.

[0071] The results are as follows Fig.10 and 11 As shown in the figure, compared with the ones without pre-sodium treatment, the specific capacity, coulombic efficiency and energy density of the sodium manganese iron pyrophosphate full battery with 8wt% sodium oxide added are significantly improved, and the energy density can reach 226Wh / kg. The cycle results of 100 cycles at 0.1C show that the cycle performance has also been improved to a certain extent, showing certain application prospects.

[0072] 4.3 Replacement of other additives

[0073] In order to further reduce costs and improve safety, referring to the method in 4.1, 8wt% of sodium carbonate (Na2CO3) was added as a pre-sodiumizing agent to prepare a sodium carbonate pre-sodiumized sodium manganese iron phosphate pyrophosphate positive electrode sheet, and then a full battery was prepared and electrochemically tested according to the method in Example 3. In addition, after the test, a simple puncture test was performed on the assembled soft-pack battery, using a sharp tool to pierce the assembled full battery from the middle, and the phenomenon was observed to verify its safety.

[0074] The results are as follows Fig.12 and 13 As shown in the figure, when the pre-sodium agent is replaced by sodium carbonate, the battery performance is not significantly affected, and better performance is achieved than the battery without pre-sodium. The puncture test results show that the soft-pack battery did not catch fire or generate heat, proving that the battery has good safety. This new type of positive electrode material has the characteristics of good air stability, high operating voltage (3.4V), good rate performance, stable cycle stability, etc., and has broad application prospects.

[0075] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a sodium ferromanganese phosphate pyrophosphate positive electrode material, characterized in that The steps include: (1) dissolving sodium dihydrogen phosphate, manganese acetate and ferric nitrate in water, adding citric acid monohydrate, heating and stirring, and drying to obtain a mixed precursor; (2) Pre-calcining the mixed precursor obtained in step (1) under an inert atmosphere, cooling it, and then calcining it again under a reducing atmosphere to finally obtain the sodium manganese iron phosphate pyrophosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The molar ratio of sodium dihydrogen phosphate, manganese acetate and ferric nitrate in step (1) is 1-5:1-3:0.1-1.

3. The preparation method according to claim 1, characterized in that: The ratio of the amount of citric acid monohydrate described in step (1) to the total amount of sodium dihydrogen phosphate, manganese acetate and ferric nitrate is 1-2:1-2.

4. The preparation method according to claim 1, characterized in that: The heating and stirring conditions in step (1) are stirring at 70 to 90° C. for 20 to 40 minutes; The drying in step (1) is freeze drying.

5. The preparation method according to claim 1, characterized in that: The inert atmosphere in step (2) is an argon atmosphere; The pre-calcination conditions in step (2) are to increase the temperature to 250-350° C. at a rate of 3-7° C. / min and calcine for 4-6 hours.

6. The preparation method according to claim 1, characterized in that: The reducing atmosphere in step (2) is a hydrogen-argon mixed atmosphere; The calcination conditions in step (2) are to increase the temperature to 600-700° C. at a rate of 3-7° C. / min and calcine for 8-12 hours.

7. A sodium iron manganese phosphate pyrophosphate positive electrode material, characterized in that: Its composition is Na3(Mn 0.8 Fe 0.2 )2(PO4)(P2O7).

8. Use of the sodium ferromanganese phosphate pyrophosphate positive electrode material according to claim 7 in the preparation of sodium batteries.

9. A sodium battery, characterized in that: The positive electrode comprises the sodium manganese iron phosphate pyrophosphate positive electrode material as described in claim 7.

10. The sodium battery according to claim 9, characterized in that: The negative electrode material of the sodium battery is hard carbon; The sodium battery has a positive electrode composed of sodium iron manganese phosphate pyrophosphate positive electrode material, SuperP and PVDF; The sodium battery, the positive electrode also includes a pre-sodiumizing agent, sodium oxide or sodium carbonate.

Citation Information

Patent Citations

  • Positive electrode material for sodium-ion battery and preparation method thereof

    CN108046231A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117059786A

  • Iron-deficient manganese-doped sodium battery positive electrode material as well as preparation method and application thereof

    CN118610454A

  • Positive electrode active material, methods for the manufacture thereof, and electrochemical cell comprising the positive electrode active material

    US20190140265A1